ANALYSIS OF THE EFFECT OF WORK COMMITMENT, ORGANIZATIONAL CULTURE AND EMPLOYEE PERFORMANCE ON THE QUALITY OF PUBLIC SERVICES: (Case Study of Employees of the Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Salatiga and Kab. Semarang) - Bernadeth Chantika Putri; Noni Setyorini; Ika Indriasari (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study was conducted with the aim of determining the effect of work commitment, organizational culture and employee performance on the quality of public services at the Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu of Kota Salatiga and Kab. Semarang. The data collection technique used primary data by distributing questionnaires to 73 respondents. In this study, all members of the population were taken as samples, in other words, the sampling method used in the study was saturated/census sampling. The results of this study indicate that the work commitment variable has a t count of 6.738> 1.993, a regression coefficient value of 0.334 with a significance of 0.000 <0.05. The organizational culture variable has a t count of 4.411> 1.993, a regression coefficient value of 0.298 with a significance of 0.000 <0.05 and employee performance has a t count of 2.014> 1.993, a regression coefficient value of 0.106 with a significance of 0.48 > 0.05. It can be concluded that work commitment has a positive and significant influence on the quality of public services, organizational culture has a positive and significant influence on the quality of public services and employee performance has no significant influence on the quality of public services.